Sex-Interacting mRNA- and miRNA-eQTLs and Their Implications in Gene Expression Regulation and Disease - Shen, Jiangshan J.; Wang, Yong-Fei; Yang, Wanling (Frontiers in Genetics, 2019)
Despite sex being an important epidemiological and physiological factor, not much is known about how sex works to interact with genotypes to result in different phenotypes. Both messenger RNA (mRNA) and microRNA (miRNA) may be differentially expressed between the sexes in different physiological conditions, and both may be differentially regulated between males and females. Using whole transcriptome data on lymphoblastoid cell lines from 338 samples of European origin, we tried to uncover genes differentially expressed between the two sexes and sex-interacting expression quantitative trait loci (ss-eQTLs). Two microRNAs were found to be differentially expressed between the 2 sexes, both of which were found to be functionally implicated in breast cancer. Using two stage linear regression analysis, 21 mRNA ss-eQTL and 3 miRNA ss-eQTLs were discovered. We replicated two of the mRNA ss-eQTLs (p < 0.1) using a separate dataset of gene expression data derived from monocytes. Three mRNA ss-eQTLs are in high linkage disequilibrium with variants also found to be associated with sexually dimorphic traits. Taken together, we believe the ss-eQTLs presented will assist researchers in uncovering the basis of sex-biased gene expression regulation, and ultimately help us understand the genetic basis of differences in phenotypes between sexes.